Psychological adjustment in cybervictims and cyberbullies in secondary education - Cañas, Elizabeth; Estévez, Estefania; Marzo, Juan C.; Piqueras, José A. (Anales de Psicología / Annals of Psychology, 2019)
The rise of cyberbullying among high school students and the importance of certain variables of psychological adjustment for the comprehension of this type of violent behavior both in bullies and in victims. This work aims to analyze the psychological profile of individuals involved in situations of cyberbullying, both victims and bullies. The adjustment variables analyzed were self-concept, perceived stress, loneliness, depressive symptomatology, social anxiety, life satisfaction, and emotional intelligence. Using a sample of 1318 adolescents (47% boys), aged between 11 and 18 years (M = 13.8, SD = 1.32), three contrast groups were established for cybervictims (severe cybervictims, moderate cybervictims, and non-cybervictims) and three groups for cyberbullies (severe cyberbullies, moderate cyberbullies, and non-cyberbullies). The results obtained through analysis of variance showed that both cybervictims and cyberbullies show deterioration in most of the studied dimensions, albeit with a different profile. Severe cybervictims showed higher scores in perceived stress, loneliness, depression, and social anxiety, and lower scores in self-concept, life satisfaction, and emotional intelligence, in comparison with non-cybervictims. Severe cyberbullies obtained higher scores in perceived stress, loneliness, and depression, and lower scores in self-concept and life satisfaction, compared to non-cyberbullies. These results allow deepening our comprehension of cyberbullying among students to improve preventive and intervention programs in schools.